The development of the Questionnaire of (Central) Auditory Processing: a screening tool of auditory processing - Tabone, Nadine; Grech, Helen; Bamiou, Doris-Eva (Frontiers in Audiology and Otology, 2024)
Objective The aim of this study was to develop a screening questionnaire for auditory processing disorder (APD) targeted for the Maltese pediatric population. Method The questionnaire consisted of 25 close-ended questions in which parents rated their child's listening skills. The data was collected from 101 typically developing Maltese bilingual children and 30 children forming a clinical group, aged between 7;00 and 9;11 years. Results The tool was found to be highly reliable with an internal consistency of 0.92 and test-retest reliability of 0.94. Significant differences emerged between normal and clinical groups (p = < 0.001). Correlational analysis demonstrated a significant correlation between the Questionnaire of (Central) Auditory Processing (QCAP) and the speech-in-noise test, Duration Patterns Test and tests of dichotic listening. Conclusion The QCAP is potentially an effective screening tool for highlighting listening difficulties in Maltese children at risk of having APD.